Glucose-6-Phosphate Dehydrogenase Deficiency By Methylation Mediated Gene Silencng Provides Resistance Against Falciparum Malaria - TABISH QIDWAI,; FARRUKH JAMAL, (International Journal of Pharma and Bio Sciences, 2012)
Malaria is the third most obivious cause of mortality in the world and is an example of evolutionary selection. Several host genetic factors have been selected in response to P. falciparum infection, such as hemoglobin variants, glucose-6-phosphate dehydrogenase (G6PD) and pyruvate kinase deficiency. Among these, G6PD deficiency is an important factor that provides resistance against malaria. Therefore, it is important to evaluate the effect of factors causing the deregulation of gene contributing to the deficiency of enzyme. Epigenetic changes are the most important factor that causes the gene silencing. We have predicted the methylation of CpG Iceland in G6PD and compared it with other genes. Based on this prediction, our hypothesis is that high promoter methylation causes epigenetic silencing of G6PD gene, which provides resistance against the falciparum malaria.